(untitled) (Revista de Investigaciones Universidad del Quindío, 2019)
During two years, it has been collected data on the epidemiological condition of foodborne diseases in four municipalities of Quindío. During this time, 32 collective cases were presented involving 240 people of different age groups from the cities of Calarcá, Tebaida, Montenegro and Quimbaya. It allowed us to propose strategies to promote the investigation of outbreaks such as the implementation of an epidemiological surveillance strategy. The variables studied were defined according to the notification form of collective cases: gender, age, township, population group, date of exposure, hospitalization, food consumed, signs, symptoms, and laboratory results. In this study, the information recorded in the notification form was analyzed. As a result, we found that the records are incomplete. It demonstrates failures in the continuous information processes of ETA outbreaks. It was not possible to carry out timely field research. As well to take samples to advance the analyzes in the laboratory in order to determine the etiological agents about the food involved in relation to the percentage of people affected and food consumed. However, it was detected that 30.8% consumed prepared foods of lower risk in public health. Among foods of greater risk in public health the findings are: chicken 16.25% and 15% eggs. In regards of consumption locations; 37.5 % at the tourist sector followed by housing 53.1%. It is concluded that the research of determining factors and causative agents were not properly executed.